Investigation of Vanadyl Pyrophosphate Catalysts Synthesised from Three Different Routes. - T AUFIQ-YAP, Y.H.; LOOl, M.H.; HUSSEIN, M.Z.; ZAINAL, Z. (Asian Journal of Chemistry, 2010)
Three different methods were used to prepare vanadyl pyrophosphate catalysts: (i) VPO, which is the classical organic way of preparing vanadyl pyrophosphate by reacting V2O5 in a mixture of isobutanol and benzyl alcohol prior to the addition of H3PO4; (ii) VPA, the earliest way; of preparation by digesting V2O5 in concentrated HCl prior to H3PO4 addition, and (iii) VPD, the latest way of preparation by pieparing VOPO4·2H2O before reacting with isobutanol. The precursors were then calcined in n-butane/air (0.75% n-butane/air) for 75 h at 673 K. The catalysts obtained were characterised by BET surface area measurements, ICP, XRD, volumetric titration and SEM-EDAX.